Sociological Analysis of the Development Of Islamic Banks in Indonesia - Budi Sulistiyo; Tajul Arifin; Abdal (Zona Law And Public Administration Indonesia, 2023)
This research is a literature study that aims to analyze the development of Islamic banks in Indonesia from a sociological perspective. Islamic banks, operating based on Islamic sharia principles, have played an important role in the transformation of the financial sector in Indonesia. However, the role of Islamic banks does not only reflect financial aspects, but also reflects the broader social and cultural dynamics in Indonesian society. This research methodology is based on a literature study involving searching, selecting, and analyzing relevant literature related to the development of Islamic banks in Indonesia. Data is obtained through literature search in various sources, including academic databases, scientific journals, books, and research reports. The results of this literature analysis will include an in-depth understanding of the sociological aspects that influence the development of Islamic banks in Indonesia. This includes the role of culture, social factors, as well as the social and economic impact of the development of Islamic banks. The main findings will be synthesized and presented in this study to provide a comprehensive picture of the dynamics of Islamic bank development in the social context of Indonesian society. This research is expected to provide valuable insights for stakeholders in the Islamic financial sector, as well as policy makers who seek to understand the role of Islamic banks in the social and economic transformation of Indonesian society. The study also provides the basis for further research focusing on the role of sociology in the context of Islamic banking in Indonesia